2019
DOI: 10.21577/1984-6835.20190130
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Potential of the Propolis of Melipona Quadrifasciata as a Preservative for Craft Beer

Abstract: Potencial Antioxidante da Própolis de Melipona Quadrifasciata como Conservante de Cerveja Artesanal Resumo: Propolis é uma mistura complexa estudada devido à suas propriedades biológicas, mas frequentemente aquela produzida pela abelha Apis melifera. Poucos estudos foram realizados, proporcionalmente, com própolis de abelhas nativas brasileiras, uma vez que se sabe que a composição química da própolis varia de acordo com a espécie de abelha que a produz. O potencial antioxidante do extrato de própolis da abelh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…The higher the percentage recorded means the extract has a higher antioxidant activity. Our results are in accordance to those that have been reported in different stingless bee species [ 44 ]. Propolis has been reported to be a good source of natural antioxidants as a result of its rich phytochemical composition [ 43 ].…”
Section: Discussionsupporting
confidence: 93%
“…The higher the percentage recorded means the extract has a higher antioxidant activity. Our results are in accordance to those that have been reported in different stingless bee species [ 44 ]. Propolis has been reported to be a good source of natural antioxidants as a result of its rich phytochemical composition [ 43 ].…”
Section: Discussionsupporting
confidence: 93%
“…They observed that the craft beer produced with this probiotic yeast had higher antioxidant activity, lower alcohol content, similar sensory characteristics, higher yeast viability, faster yeast growth, and a stronger acidification than the beer fermented by S. cerevisiae strains usually employed in brewing. The nutritional benefits of craft beer can be consistently increased by the addition of ethanolic extract of propolis after fermentation and maturation, resulting in higher phenolic and flavonoid content, higher antioxidant activity (Ulloa et al., 2017), and increased shelf life thanks to oxidation inhibition without changes of the organoleptic characteristics (Galgowski, Fischer, Simionattoa, Guedes, & Cordova, 2019). Bioactive compounds detected in craft beer, namely, phenolic compounds, can also provide antiviral activity.…”
Section: Safety and Healthiness Of Craft Beermentioning
confidence: 99%